PENGARUH PENGEMBANGAN KARIR, IKLIM ORGANISASI, DAN KEPUASAN KERJA TERHADAP PROFESIONALITAS KARYAWAN UNIVERSITAS NEGERI - Suti, Marus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2015)
Abstract: The staff’s professionalism is assumed to be affected by the variation their career Development, organizational climate and their job satisfaction. The aim of the experimental study reported here was to test the hypothesis. The causal study was conducted in Makassar State University, from June to October 2009, involving a sample of 120, which had been selected from the overall 566 staff members of the university, by using the simple random sampling technique. Data of each variabel were collected through a survey and analysed descriptively and inferentially through the path analysis. Results show direct and positive effects of career development and organisational climate, respectively, on their job satisfaction. Result alto show indirect effects of the staff’s career development on the professionalism through job satisfaction, and of organizational climate on the staff’s career development, job satisfaction, and their perception of the organizational climate in the strategis Plan of Makassar State University to improve profesional human resource. Abstrak: Keprofesioanalan staf diasumsikan dapat dipengaruhi oleh variasi pengembangan karier mereka, iklim organisasi, dan kepuasan kerja merak. Tujuan dari penelitian eksperimen ini adalah untuk menguji hipotesis. Penelitian ini dilaksanakan di Universitas Negeri Makassar, dari bulan Juni hingga Oktober 2009, yang melibatkan 120 sampel, yang dipilih dari 566 anggota staf Universitas, dengan menggunakan teknik simple random sampling. Data dari masing-masing variabel dikumpulkan melalyi survey dan analisis secara deskriptif dan inferensial melalui path analysis. Hasil menunjukkan secara langsung dan positif pengaruh dari pengembangan karier dan iklim organisasi pada pengembangan karier staf, kepuasan kerja, dan persepsi mereka terhadap iklim organisasi dalam rencana strategis dai Universutitas Negeri Makassar untuk meningkatkan sumber manusia yang profesional.